Price-quality interaction on the formation of buying interest of apartment customers - Gofur, Abdul; Sari, Santi Retno (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2024)
This study aims to investigate the interaction between price and quality in the context of apartment purchasing and its impact on consumer purchase intention. This research makes an important contribution to financial management and decision making regarding apartment purchases. The findings from this research provide valuable insight into how the information consumers receive influences their purchasing behavior, as well as how the relationship between price and quality can influence consumer perceptions. The implications of this research can provide guidance for real estate professionals and prospective apartment buyers in making more informed decisions. Thus, this study makes a significant contribution to understanding the dynamics of the property market and consumer behavior regarding apartment purchases.